AJI a web service security framework - Aclan, Alegria
Web services are designed for the standardization and interoperability of web applications, regardless of the platforms and languages they use. This paper discusses the web service and its security implications and presents a framework that would facilitate a secure communication between web applications and their service provider. The proposed security framework was initially implemented to address the needs between the University of the Philippines' Computerized Registration System and the UP College of Law. The results of the implementation are provided, as well as specific recommendations to further improve the framework. Our design and results show the intricacies of designing a web service framework for an enterprise-grade web application.